Thomson Effect, Leg Design, Heat Interaction, and Material Impacts on Segmented Thermoelectric Cooler: Insights from Three-Dimensional Simulation - Mani A.; Sarkar J. (My University, 2025)
Thermoelectric coolers (TECs) have emerged as promising cooling solutions; however, their relatively low coefficient of performance (COP) remains challenging. Hence, to better understand the factors influencing TEC efficiency and to guide the design of more effective systems, a three-dimensional numerical model is developed. It includes temperature-dependent thermoelectric properties (Thomson effect) and convective-radiative heat interactions. This study explores the TEC performance by analyzing various leg configurations, such as segmented and non-segmented legs, with constant and variable cross section using different material compositions to maximize the cooling effect and COP. Cylindrical legs outperformed conventional square legs, offering a 3% increase in COP and 2.5% in cooling effect. The non-segmented legs emphasize the need for condition-specific material selection, while segmented legs show up to 6.3% higher COP and 5.5% better cooling effect at lower currents, with performance declining at higher currents. A larger temperature lift between the hot and cold sides reduces TEC efficiency. The material-specific segmented leg length ratio can be optimized for maximum performance. A uniform circular leg cross section is more effective than a variable one. Incorporating the temperature-dependent material properties and the Thomson effect in the model significantly increases the TEC performance (up to 30%). Similarly, considering convective-radiative heat interaction in the model increases the performance (about 10%). These two inclusions enhance the accuracy of performance prediction of the model used in this study. These findings provide valuable insights for designing TECs according to application and operating conditions. Copyright © 2025 by ASME.